2019
DOI: 10.1177/1932296819832876
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Based Infusion System: Advancing the Development

Abstract: Background: Deviations in glucose control in critical care have been shown to increase mortality and morbidity. However, optimal glucose control through present technologies has shown to be a challenge. The insulin balanced infusion system (IBIS) is a new and emerging technology. Methods: The closed loop system was tested in a stress trial to evaluate glucose stability in response to various conditions in nonrandomized people with type 1 diabetes mellitus (n=12). The prototype used in this trial was based on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…An adaptive counterbalancing system by Admetsys (Admetsys Corporation, Boston MA) has been shown in clinical trials of 43 insulin-requiring diabetic individuals to control plasma glucose in a target range of 4.4–6.9 mmol/L for 97% of the time without hypoglycemia (<3.9 mmol/L) during protocols which attempted to destabilize glucose control. 73 , 74 Additional in silico studies have confirmed a similar counterbalancing algorithm that achieves comparable results. Based on a total of 126,000 5-day simulations using 107,000,000 glucose samples, the time in target range (3.9–7.8 mmol/L) was 97.8%, hyperglycemia (>7.8 mmol/L) was noted 2.1% and hypoglycemia (<3.9 mmol/L) 0.09%.…”
Section: Introductionmentioning
confidence: 85%
“…An adaptive counterbalancing system by Admetsys (Admetsys Corporation, Boston MA) has been shown in clinical trials of 43 insulin-requiring diabetic individuals to control plasma glucose in a target range of 4.4–6.9 mmol/L for 97% of the time without hypoglycemia (<3.9 mmol/L) during protocols which attempted to destabilize glucose control. 73 , 74 Additional in silico studies have confirmed a similar counterbalancing algorithm that achieves comparable results. Based on a total of 126,000 5-day simulations using 107,000,000 glucose samples, the time in target range (3.9–7.8 mmol/L) was 97.8%, hyperglycemia (>7.8 mmol/L) was noted 2.1% and hypoglycemia (<3.9 mmol/L) 0.09%.…”
Section: Introductionmentioning
confidence: 85%
“…The future may see technology continue to advance to where closed-loop systems may be utilized that continuously monitor glucose levels and automatically communicate with the insulin distribution system and adapt to changing insulin requirements. Preliminary studies have demonstrated the ability to achieve and maintain blood glucose goals safely [35]. Larger studies in critical care populations may be needed to assess the utility and economic feasibility of these technologies.…”
Section: Insulin Therapymentioning
confidence: 99%